Racial Wealth Disparities: Is the Gap Closing? - Maury Gittleman; Edward N. Wolff (Levy Economics Institute of Bard College, 2000)
A vast literature in economics has examined the economic progress of African Americans during this century. Most of these studies have focused on income–or on even narrower measures of economic well-being, such as earnings–to assess the extent to which any gains made relative to other racial groups can be attributed to such factors as declining racial discrimination, affirmative action policies, changes in industrial composition, or a narrowing gap between the educational levels of African Americans and the rest of the population. However, studies of earnings and income, while important for assessing the extent to which labor market discrimination exists and the ability of African Americans to move closer to whites in terms of acquiring the skills and connections that are currently rewarded by the markets, provide an incomplete picture. This paper therefore explores how African Americans have fared in terms of wealth, a less well-known factor and an important measure of economic well-being.
Keywords: 330